A fresh “slant” on modified Mitchell bladder neck reconstruction: A contemporary single-institution experience - Bowen, Diana K.; Cheng, Earl Y.; Hirsch, Josephine; Huang, Jason; Meyer, Theresa; Rosoklija, Ilina; Chu, David I.; Yerkes, Elizabeth B. (Frontiers in Pediatrics, 2022)
Introduction: Patients with neurogenic urinary incontinence due to an incompetent outlet may be offered bladder neck reconstruction, but the quest for the perfect surgical outlet procedure continues. Our aim was to characterize continence and complications after modified Mitchell urethral lengthening/bladder neck reconstruction (MMBNR) with sling and to introduce a modification of exposure that facilitates subsequent steps of MMBNR. Methods: A single-institution, retrospective cohort study of patients who underwent primary MMBNR between May 2011-July 2019 was performed. Data on demographics, urodynamic testing, operative details, unanticipated events, continence, bladder changes, and additional procedures were collected. A 2013 modification that permits identification of the incompetent bladder neck prior to urethral unroofing was applied to the last 17 patients [Figure 1]. The trigone and bladder neck are exposed via an oblique low anterolateral incision on the bladder. Ureteral reimplantation is not routinely performed. Focal incision of the endopelvic fascia after posterior plate creation limits breadth of blunt dissection for sling placement. Descriptive statistics were utilized. Results: Twenty-five patients (13 females) had MMBNR with sling at a median age of 10 years (interquartile range [IQR] 8, 11). Bladder augmentation was performed concurrently in 14/25 (56%) patients. At a median of 5.0 (IQR 3.9-7.5) years follow-up after MMBNR, 9/11 (82%) without bladder augmentation and 13/14 (93%) with bladder augmentation had no leakage per urethra during the day without further continence procedures. Of the 3 patients with persistent incontinence, two achieved continence with bladder wall Botox injection (overall continence 24/25, 96%). New and recurrent vesicoureteral reflux was noted in 5 and 1 patients, respectively. Two patients required subsequent bladder augmentation for pressures and 1 other will likely require it. None have required bladder neck closure or revision. Conclusion: MMBNR with sling provides promising continence per urethra in neurogenic bladder with low need for secondary continence procedures. Ongoing modifications may achieve elusive total continence.